PENGGALIAN POTENSI WISATA RELIGI DAN SEJARAH MAKAM PANJANG - Indah Karina Yulina (BAKTIMU : Jurnal Pengabdian Kepada Masyarakat, 2021)
The Long Tomb is located in Drajat Village, Kesambi District. The Drajat village area has several potential for pilgrimage tourism, namely in the form of graves and makom which contributed to the spread of Islam in Cirebon around the 15th century, especially in the spread of Islam in the Drajat village. In this article, we focus on the potential for long tombs to be used as potential for religious tourism. The purpose of this study is to describe religious tourism and the meaning of pilgrimage at the Long Tomb. The research method used is descriptive qualitative, by conducting in-depth interviews with the caretaker as the source of the long tomb. The Long Tomb is the resting place of a figure of Sultan Lelana who is known by the public as Prince Jaka Lelana. Jaka Lelana is the second son of Sunan Gunung Jati. The Long Tomb is sacred because Jaka Lelana is a descendant of the Guardian and is the son of Sunan Gunung Jati. Currently, the potential for long tomb pilgrimages is still very minimal and poorly maintained, so a strategy is needed to disseminate the potential to become one of the pilgrimage tourist destinations in Cirebon City.